2003
DOI: 10.2172/15003956
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Aerodynamic Analyses of Six Airfoils for Use on Small Wind Turbines: July 11, 2002--October 31, 2002

Abstract: The U.S. Department of Energy (DOE), working through its National Renewable Energy Laboratory (NREL), is engaged in a comprehensive research effort to improve the understanding of wind turbine aeroacoustics. Motivation for this effort is the desire to exploit the large expanse of low wind speed sites that tend to be closer to U.S. load centers. Quiet wind turbines are an inducement to widespread deployment, so the goal of NREL's aeroacoustic research is to develop tools for use by U.S. industry in developing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 2 publications
1
30
0
Order By: Relevance
“…Although the same shape of the drag polars was observed in both cases, showing the appearance of the laminar separation bubble, the drag coefficients for a given lift coefficient were found to be higher in the measurements by Selig and McGranahan (2004). Interestingly, a similar discrepancy, limited to the low Reynolds number case of 100,000, was found in a theoretical analysis of small-scale wind turbine airfoils (Somers and Maughmer, 2003), including the Eppler airfoil E387 mentioned above. In their study, the authors use two different airfoil codes, the XFoil and the Eppler Airfoil Design and Analysis Code (Profil00), finding similar results for drag polars, except for the low Reynolds number case of 100,000, where the experimentally observed drag is better reproduced by the Profil00 code.…”
Section: Rotor Aerodynamics and Loadssupporting
confidence: 64%
“…Although the same shape of the drag polars was observed in both cases, showing the appearance of the laminar separation bubble, the drag coefficients for a given lift coefficient were found to be higher in the measurements by Selig and McGranahan (2004). Interestingly, a similar discrepancy, limited to the low Reynolds number case of 100,000, was found in a theoretical analysis of small-scale wind turbine airfoils (Somers and Maughmer, 2003), including the Eppler airfoil E387 mentioned above. In their study, the authors use two different airfoil codes, the XFoil and the Eppler Airfoil Design and Analysis Code (Profil00), finding similar results for drag polars, except for the low Reynolds number case of 100,000, where the experimentally observed drag is better reproduced by the Profil00 code.…”
Section: Rotor Aerodynamics and Loadssupporting
confidence: 64%
“…2D Navier-Stokes solver (EllipSys2D) and potential Panel method codes (XFOIL, PROFIL [56]) are widely utilized for airfoil analysis before the pre-stall by renowned wind turbine research organizations including NREL [57] and Risoe [58]. Raciti Castelli et al [59] extended the experimental data from Sheldahl and Klimas [49] using the Xfoil.…”
Section: Direct Design Approachmentioning
confidence: 99%
“…The blade used in this paper is a tip airfoil (S822) and mainly designed for wind turbines rated between 2-20kW [6]. The values of l C and d C for a Reynold number of 0.7×10 6 is considered in this study and found from the available published data [7].…”
Section: Dependence Of Power Coefficientmentioning
confidence: 99%